The changing content of design vocabulary in upholstery fabrics between originality and modernity (Journal of the College of Basic Education, 2022)
Cloth Design Is Considered The Most Important Filed To Determine The Artistic , The Traditional And Cultural Features For Each Element , That Resemble The Content Changed Unit In Design Furnishing Cloth That Has Philosophical And Reference To Shop Units .According To That It Is Necessary The Designer Should Put In His Mind That The Importance Of That Content Is In Being Result Of Many Mental Powers And Action That Deal With Hot Treated With To Accomplish New Responses That Have The Sense Of Accuracy And Realism That Can Be Realized Through The Artistic Ways That Related In Tangible Way . From This Point Comes The Study Of The Subject The Changed Content Of The Design Unit In Furnishings Cloth Between Modern And Genuineness . This Study Contains Four Chapter , The First Chapter Contains The Problem , Importance , Aims And The Research Limits And Then Determines Terms The Problem Lined Out According To The Following Question : Is There A Role For The Changed Content Of Design Units In Designing Furnishings Cloth Between Modernism And Genuineness .The Second Chapter Includes Two Parts , The First One Deals With The Meaning Of Shape Content In Furnishing Cloth , Change Is A Positive Role In The Design Of Furnishing Cloth . The Means To Be Different From The Context .The Second Part Contains The Changed Content Between Modern Ism And Genuieness In The Design Of Furnishing Cloth Then Concluded Indicators That Resulted In Theoretical Framework That The Researcher Depends On To Make Analyze From Then The Former Studying .The Third Chapter Contains The Prefectures Of The Research And The Method Of The Research That Is A Descriptive Analyse Approach .(5) Samples Has Been Choosen From . The Forth Chapter Contains The Result Of Samples Analysis .